PERANCANGAN ALGORITMA PENCARIAN RUTE PERJALANAN KENDARAAN LISTRIK DENGAN ALGORITMA A-STAR YANG DIMODIFIKASI UNTUK EFISIENSI BATERAI - Mudhoffar, Zakki
Electric vehicles (EVs) are critical in the shift to environmentally friendly practices, especially in the transportation industry. However, the main obstacle limiting the range and practicality of electric vehicles is the efficiency of battery use. The goal of this research is to create an optimized EV-specific route-finding algorithm with an emphasis on battery efficiency. To find the most energy-efficient route, the height parameters of topographic data are integrated into the traditional A* (A-star) method. This methodology combines real scenario-based simulation design from the ITB Campus to Bandung Station with theoretical analysis and collection of related data, such as electric vehicle and battery parameters. The results show that choosing a route based on traffic and altitude can determine the energy use of an electric vehicle, resulting in a longer EV range estimate. This discovery encourages wider use of electric vehicles and reduces the environmental impact of vehicle traffic.